Speech Language Therapy in Special Schools of Punjab: A Study of Auditory Profiles of Children with Hearing Impairment - Hina Noor, Nasim Akhter Raja (JIE, 2024)
Speech therapy services are targeted to develop auditory skills in children with hearing impairment (HIC) that may reflect their verbal communication potentials. The study aimed at exploring the current provisions to speech language therapists (SLTs), speech therapy practices and auditory profiles of HIC through a survey of public special education institutions of the Punjab. Cluster sampling was used to collect data from SLTs working in the special education institutions of all divisions of Punjab, with the help of a self-developed questionnaire (Cronbach alpha, 0.8). Data revealed that the majority of hearing aid user HIC were not comfortable with their hearing aids. The majority of HIC in junior classes were provided with speech therapy with the frequency of 1-2 sessions per week only. They were at detection and discrimination level of speech perception. The provision of equipment and material to SLTs and their professional practices need improvement. The majority of SLTs recommended reducing the workload and increasing collaboration among rehabilitation professionals and parents. It was concluded that HIC were not getting maximum benefits from available provisions as reflected by their auditory profiles. The study recommended that improvement and monitoring of speech therapy practices may improve verbal communication potentials of HIC.